The implicit pedagogical objectives in professionalizing university training for paramedics - Benzerb, Zaïra; Haroun, Zineb (Journal of Human Sciences, 2025)
The title “Linguistic Remediation / Techniques of Oral and Written Expression” for the FLE module, intended for first-year students in the LMD professional bachelor’s program in paramedical sciences, poses a challenge for instructors as it brings together two distinct didactic paradigms in FLE. The examination of the course units reveals a discrepancy between the course’s purpose and its explicitly stated objectives, raising questions about its pedagogical intentions. This qualitative, descriptive, and analytical research aims to identify the implicit objectives and the hidden curriculum through the analysis of teaching organization sheets and the detailed program. The results show that these implicit objectives primarily target the development of transversal linguistic skills and autonomy in academic and professional writing for the students.